2005
DOI: 10.1063/1.2006675
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and rovibronic spectra of the T-shaped and linear ground-state conformers of a weakly bound rare-gas–homonuclear dihalogen complex: He⋯Br2

Abstract: Laser-induced fluorescence spectra of Br(2) entrained in a He supersonic expansion have been recorded in the Br(2) B-X, 8-0, 12-0, and 21-0 spectral regions at varying downstream distances, and thus different temperature regimes. Features associated with transitions of the T-shaped and linear He...Br(2)(X,nu(") = 0) complexes are identified. The changes in the relative intensities of the T-shaped and linear features with cooling in the expansion indicate that the linear conformer is energetically more stable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 33 publications
9
35
0
Order By: Relevance
“…This is most likely due to the spectral congestion when exciting the linear conformer to the highly delocalized intermolecular vibrational levels in the excited state, as they are very close in energy. 9 Further, in these studies, the analysis of the pressure and temperature dependence indicates the higher stability of the (1,1) isomer with respect to the (2,0), as predicted by the 5D variational calculations 29 and confirmed in this work by the 6D MCTDH results (see Table V). The binding energy of the different isomers is 32.21, 31.22, and 30.29 cm −1 , for the (0,2), (1,1), and (2,0) isomers, respectively.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…This is most likely due to the spectral congestion when exciting the linear conformer to the highly delocalized intermolecular vibrational levels in the excited state, as they are very close in energy. 9 Further, in these studies, the analysis of the pressure and temperature dependence indicates the higher stability of the (1,1) isomer with respect to the (2,0), as predicted by the 5D variational calculations 29 and confirmed in this work by the 6D MCTDH results (see Table V). The binding energy of the different isomers is 32.21, 31.22, and 30.29 cm −1 , for the (0,2), (1,1), and (2,0) isomers, respectively.…”
Section: Resultssupporting
confidence: 68%
“…However, based on a sum of the experimental values of the binding energy of the linear (0,1) and T-shape (1,0) triatomic conformers, Boucher et al proposed binding energies of 33.6(1.1) and 33.2(1.1) cm −1 for the (1,1) and (2,0) He 2 Br 2 complexes, respectively. 9 According to our calculations, the assumption of neglecting the He-He interaction does not affect the relative stability of the different conformers, with differences between the 6D result and the sum of the theoretical triatomic binding energies (see Table V) for the (0,2), (1,1), and (2,0) isomers, respectively. However, it has been shown that this assumption fails for systems such as He 2 I 2 , where the competition of the smaller differences between the linear and T-shape triatomic binding energies and the rotational effects results in a change of the relative stability of the isomers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations